2021
DOI: 10.1016/j.wnsx.2021.100103
|View full text |Cite
|
Sign up to set email alerts
|

Improving Neurosurgery Education Using Social Media Case-Based Discussions: A Pilot Study

Abstract: Background The increasing shift toward a more generalized medical undergraduate curriculum has led to limited exposure to subspecialties, including neurosurgery. The lack of standardized teaching may result in insufficient coverage of core learning outcomes. Social media (SoMe) in medical education are becoming an increasingly accepted and popular way for students to meet learning objectives outside formal medical school teaching. We delivered a series of case-based discussions (CbDs) over SoMe to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…A discrepancy in perception between Western countries and low-to middle-income countries (LMICs) is sometimes observed: in fact, the ability to transfer knowledge and decision-making skills among colleagues, using social media in promoting the concept of “global” education, is advocated and beneficial especially for the clinicians from LMICs, 12 , 13 while it remains uncertain in Western countries due to the high educational offers. More than the concept of general value of a single webinar, it would be more important to ask: “What benefits do webinars offer you?”.…”
mentioning
confidence: 99%
“…A discrepancy in perception between Western countries and low-to middle-income countries (LMICs) is sometimes observed: in fact, the ability to transfer knowledge and decision-making skills among colleagues, using social media in promoting the concept of “global” education, is advocated and beneficial especially for the clinicians from LMICs, 12 , 13 while it remains uncertain in Western countries due to the high educational offers. More than the concept of general value of a single webinar, it would be more important to ask: “What benefits do webinars offer you?”.…”
mentioning
confidence: 99%
“…As a consequence, we have observed that 76.3% of students would benefit from online seminars and other educational events accessible remotely, which in our country have been promoted also by the Italian Society of Neurosurgery (SINch). Recent studies have analyzed these innovative instruments, proposing that they could have a positive impact, increasing students' knowledge and self-confidence in managing neurosurgical patients ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the large availability of neurosurgical videos on social media, YouTube channels, national scientific societies websites, but also of simulators and of exercises to improve manual skills with daily use objects (i.e., eggs, chicken wings, etc.) would permit a larger number of students to be exposed also to the most technical parts of the neurosurgical activities ( 23 25 ). However, we consider that such exposure requires to be guided and commented on by a mentor, to avoid the risk that students would wrongly consider the challenges of this surgery ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, during complex surgical procedures, neurosurgeons can use social networks to share information and receive feedback from their peers, helping to improve patient outcomes and decrease the risk of complications. Additionally, social networks can supply a platform for neurosurgeons to discuss difficult cases, request advice from colleagues, and receive support from their peers ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%